Assessing assumptions for statistical analyses in randomised clinical trials. Issue 5 (4th April 2019) - Nielsen, Emil Eik; Nørskov, Anders Kehlet; Lange, Theis; Thabane, Lehana; Wetterslev, Jørn; Beyersmann, Jan; de Uña-Álvarez, Jacobo; Torri, Valter; Billot, Laurent; Putter, Hein; Winkel, Per; Gluud, Christian; et al.
Abstract : In order to ensure the validity of results of randomised clinical trials and under some circumstances to optimise statistical power, most statistical methods require validation of underlying statistical assumptions. The present paper describes how trialists in major medical journals report tests of underlying statistical assumptions when analysing results of randomised clinical trials. We also consider possible solutions how to improve current practice by adequate reporting of tests of underlying statistical assumptions. We conclude that there is a need to reach consensus on which underlying assumptions should be assessed, how these underlying assumptions should be assessed and what should be done if the underlying assumptions are violated.